'Go humbly dressed as befits servants of God': Alcuin, clerical identity, and sartorial anxieties. Issue 2 (16th April 2018) - Garver, Valerie L.
Abstract : Employing clothing as a means to investigate the letters of Alcuin (d. 804) reveals not only his great interest in dress as a subject for moral instruction but also ways in which the clothing and textiles of his time shaped Alcuin's discussion of attire. Alcuin perceived garments as both powerful tools and moral dangers with material consequences, particularly in his letters to Anglo‐Saxon correspondents. His epistolary corpus demonstrates sartorial tensions in a period that witnessed changes to clerical dress, increased concern to demarcate clerical from lay, and broader use of silk both in Anglo‐Saxon England and Carolingian Francia.